Understanding intercultural interaction : an analysis of key concepts - Fitzpatrick, Frank (Bingley, U.K. : Emerald Publishing Limited, 2019)
Living, working and studying in intercultural and international contexts is ever more relevant to a broad range of individuals including educators, social scientists and professionals. As education and work become increasingly international, every student and professional at some point is likely to feel the need to explore and discuss concepts of culture and identity in order to be prepared for intercultural encounters in the globalised workplace. Understanding Intercultural Interaction encourages readers to abandon the notion that culture is something static that we possess or have inherited and to see it as fluid and dynamic, created, interpreted and negotiated through social interaction. It recommends an examination of the contextual framework of intercultural behaviour and the power relations and inequalities that pervade it to enable readers to understand themselves and the role that they play on the international stage. In its exploration of key concepts in culture and interaction, the book equips students and professionals from varied backgrounds with the tools to understand, discuss and apply them to their own lives. Designed principally as an accessible introduction for non-specialists to explore a wide range of theories and ideas that seek to explain intercultural encounters, the critical analysis provided in this book also offers ample scope for more in-depth exploration by those who wish to deepen their knowledge of the field, making it ideal for facilitating reflection and discussion in study or training contexts.
Part I. Approach and principles -- Part II. Key concepts -- Index.
Includes index.
Print version record.
Keywords: Intercultural communication; Cultural relations; Social Science -- Sociology -- General; Cultural studies